2008
DOI: 10.1007/s00586-008-0603-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of morbidity, mortality and outcome following cervical spine injuries in elderly patients

Abstract: We analysed the morbidity, mortality and outcome of cervical spine injuries in patients over the age of 65 years. This study was a retrospective review of 107 elderly patients admitted to our tertiary referral spinal injuries unit with cervical spine injuries between 1994 and 2002. The data was acquired by analysis of the national spinal unit database, hospital inpatient enquiry system, chart and radiographic review. Mean age was 74 years (range 66-93 years). The male to female ratio was 2.1:1 (M = 72, F = 35)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
102
1
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 19 publications
(32 reference statements)
7
102
1
10
Order By: Relevance
“…The mortality in the follow-up phase was higher in DISH patients than in AS patients, regardless of type of treatment received. Several authors have stated that advancing age, obesity and diabetes mellitus are associated with higher mortality rates in trauma patients [13,46,53,56,72,78,84]. In addition, some authors have reported the treatment with a halo frame or other immobilization device in elderly patients with cervical fractures to be associated with higher morbidity and mortality rates [47, 71,115].…”
Section: Discussionmentioning
confidence: 99%
“…The mortality in the follow-up phase was higher in DISH patients than in AS patients, regardless of type of treatment received. Several authors have stated that advancing age, obesity and diabetes mellitus are associated with higher mortality rates in trauma patients [13,46,53,56,72,78,84]. In addition, some authors have reported the treatment with a halo frame or other immobilization device in elderly patients with cervical fractures to be associated with higher morbidity and mortality rates [47, 71,115].…”
Section: Discussionmentioning
confidence: 99%
“…28 This is a significant problem, because previous studies have shown a greater level of morbidity and death in older patients. 2,4,6,17,18,32 The debate is particularly prominent in regard to older patients with a Type II fracture with limited displacement. In this population, the risk-benefit consideration of a surgical or nonsurgical approach may be more equivocal given the increase in the complexity of these patients' overall medical and comorbidity profile.…”
Section: Discussionmentioning
confidence: 99%
“…30 A dichotomy exists between surgical and nonsurgical management of Type II odontoid fractures. Although some experts have documented very good clinical outcomes with the use of halo braces in patients with these fractures, 17,30 the halo vest was also associated with death and morbidity in several studies, 14,22,26,27,31,32 and some authors question the ability of older patients to tolerate these devices. 28 Regardless of the treatment modality, in-hospital mortality rates for patients with a Type II odontoid fracture remain significant at 10% 28 to 25%.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have found a risk of acute (inhospital) mortality of >20% for elderly patients with isolated cervical spine fractures 14,15 . While osteoporosis and ankylosis are generally thought to place elderly individuals at increased risk for cervical spine fractures 15,16 , there is little published information on the rate of mortality after these injuries. This deficiency in the literature contributes to a lack of consensus on the optimal treatment of cervical fractures in elderly individuals.…”
mentioning
confidence: 99%